1998
DOI: 10.1136/jnnp.65.6.917
|View full text |Cite
|
Sign up to set email alerts
|

Case report of unusual leukoencephalopathy preceding primary CNS lymphoma

Abstract: A previously healthy 35 year old woman presented with bilateral uveitus associated with multiple, evolving, non-enhancing white matter lesions consistent with a progressive leukoencephalopathy such as multiple sclerosis. Thirty months after her initial presentation, she was diagnosed with primary CNS lymphoma and died 14 months later. The unusual clinical course preceding the diagnosis suggests that a demyelinating disease may have preceded, and possibly heralded, the development of primary CNS lymphoma. Cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 20 publications
2
46
0
Order By: Relevance
“…Epstein-Barr virus involvement in the pathogenesis of CNS lymphoma in immunocompetent patients is less consistent. Although Epstein-Barr virus was not causative in our patients, as shown by our negative PCR studies for the Epstein-Barr virus genome, our 2 patients and those previously reported by Alderson et al [22] and Brecher et al [23] (in which "sentinel lesions" preceded diagnostic biopsies of primary CNS lymphoma by 7-11 months) suggest a common pathogenic mechanism for both the prodrome and primary CNS lymphoma. Based on those cases we have to raise the possibility that lymphocytic infiltrates that accompany leukoencephalopathy may undergo transformation to malignant B cell populations.…”
Section: Discussionsupporting
confidence: 49%
“…Epstein-Barr virus involvement in the pathogenesis of CNS lymphoma in immunocompetent patients is less consistent. Although Epstein-Barr virus was not causative in our patients, as shown by our negative PCR studies for the Epstein-Barr virus genome, our 2 patients and those previously reported by Alderson et al [22] and Brecher et al [23] (in which "sentinel lesions" preceded diagnostic biopsies of primary CNS lymphoma by 7-11 months) suggest a common pathogenic mechanism for both the prodrome and primary CNS lymphoma. Based on those cases we have to raise the possibility that lymphocytic infiltrates that accompany leukoencephalopathy may undergo transformation to malignant B cell populations.…”
Section: Discussionsupporting
confidence: 49%
“…The typical patient is male, in his seventh decade, and presents with the syndrome of a subacute mass lesion. In rare instances, PCNSL can be preceded by prodromal symptoms and even in ammatory demyelinating lesions (Alderson et al, 1996;Bender and Schapiro, 1989;Brecher et al, 1998;DeAngelis, 1990). The typical MRI features of PCNSL are isointense to hypointense and hyperintense parenchymal masses on T1-weighted, proton density, and T2-weighted scans; homogeneous and intense contrast enhancement; contact with CSF, either at the ependymal or the pial surface; and decreased contrast enhancement in patients given corticosteroids (Jack et al, 1986).…”
Section: P T-pcnslmentioning
confidence: 99%
“…PCNSL presenting as an infiltrative lesion of the brain has sometimes been misdiagnosed initially as a demyelinating disease. 10,11 In doubtful cases a tissue biopsy is essential to guide management. [12][13][14] Thus, some neurological diseases may present with Weber's syndrome, masquerading as a midbrain stroke.…”
Section: Discussionmentioning
confidence: 99%